Design of Standar Operational Procedures Teman Hati Services - Ifah Muzdalifah; Hosizah Hosizah; Noor Yulia; Ambarwati Ambarwati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Standard operational procedures as guidelines to assist officers in completing work more effectively and efficiently. Telepsychiatry services at Psychiatry Dr. Soeharto Heerdjan changed the use of the application from Jitsi Meet to Teman Hati (Telemental Health and Home Visite). Several problems were found in the Jitsi Meet application, making it difficult for patients/families to use it. Changes to the application have an impact on changes to the SOP. So that services can be well organized and carried out according to procedures, SOP are needed for implementation.Objective: Designing of standard operational procedures Teman Hati (Telemental Health and Home Visite) Methods: Research Method with use R&D (Research & Development) from November 2022 – January 2023. Data collection doing by interview FGD (Focus Group Discussion) with 13 informants. First step of research are collect information, determine method and arrange the technic of SOP, writing SOP, simulation and the last is review. Results: There are 5 draft SOPs, namely registration SOP, drug delivery SOP, teleconsultation SOP, application usage SOP for patients/families, and application usage SOP for hospital staff. The 5 SOP that were designed were simulated and reviewed by the SOP implementers and the patient's family. Conclusion: The 5 SOP designs give more easier for officers to implement of Telepsychiatry service in Psychiatry Dr. Soeharto Heerdjan Hospital and decrease the satisfaction of patient's family to the hospital. The SOP that has been designed must legitimized, socialized, monitored and evaluated.